Lithium isotopes as indicators of meteorite parent body alteration - Sephton, M.; James, R.; Fehr, M.; Bland, Phil; Gounelle, M. (John Wiley & Sons, Inc., 2013)
Hydrothermal processing on planetesimals in the early solar system produced new mineral phases, including those generated by the transformation of anhydrous silicates into their hydrated counterparts. Carbonaceous chondrites represent tangible remnants of such alteration products. Lithium isotopes are known to be responsive to aqueous alteration, yet previously recognized variability within whole rock samples from the same meteorite appears to complicate the use of these isotopes as indicators of processing by water. We demonstrate a new way to use lithium isotopes that reflects aqueous alteration in carbonaceous chondrites. Temperature appears to exert a control on the production of acetic acid-soluble phases, such as carbonates and poorly crystalline Fe-oxyhydroxides. Temperature and degree of water-rock interaction determines the amount of lithium isotope fractionation expressed as the difference between whole rock and acetic acid-leachable fractions. Using these features, the type 1 chondrite Orgueil (δ7Li(whole rock) = 4.3‰; Δ7Li(acetic-whole) = 1.2‰) can be distinguished from the type 2 chondrites Murchison (δ7Li(whole rock) = 3.8; Δ7Li(acetic-whole) = 8.8‰) and carbonate-poor Tagish Lake (δ7Li(whole rock) = 4.3; Δ7Li(acetic-whole) = 9.4‰). This initial study suggests that lithium isotopes have the potential to reveal the role of liquid water in the early solar system.